Three new species of Microlaimidae (Nematoda: Microlaimida) from intertidal sand of the Sea of Japan - Fadeeva, Natalia P.; Karpova, Alena A. (Zootaxa, 2026)
Three new species of Microlaimidae are described from the sand coast of the Sea of Japan (Russian coast). Among previously discovered free-living nematodes, the genera Microlaimus and Bolbolaimus are recorded for the first time. Bolbolaimus mirandus sp. nov. is characterised by anterior cephalic region set off from the body, large cuticularised buccal cavity with one strong dorsal tooth and two noticeable subventral teeth, muscular anterior and posterior pharyngeal bulbs, curved not cephalated spicules, short and simple gubernaculum, and short and conical tail. Bolbolaimus selinae sp. nov. has an annulated cuticle with very close and fine longitudinal bars; anterior and posterior pharyngeal bulb; large buccal cavity with one large dorsal tooth, two small subventral teeth in the anterior part, and transversal rows of protrusions in the posterior part; amphidial fovea oval shaped in males and circular shaped in females. Microlaimus asiaticus sp. nov. is characterised by monospiral amphidial fovea turning ventrally at the level of posterior part of cup-shaped buccal cavity, weakly conspicuous dorsal tooth and two small subventral protrusions; small circular pharyngeal bulb; four conical precloacal supplements in male, and conical tail. These findings expand the taxonomic knowledge and geographic distribution of Microlaimidae in the Pacific region.